Operationalizing and measuring climate change adaptation success - Henry A. Bartelet; Michele L. Barnes; Lalu A. A. Bakti; Graeme S. Cumming (Ecology and Society)
In a context of rapid global change, understanding whether and how adaptation to climate change can be considered successful has become an important research gap within the climate change adaptation literature. Although definitions of adaptation success have been formulated, it remains unclear how they can be operationalized and tested empirically. To address this gap, we operationalized one of the most prominent definitions of successful adaptation within the academic literature, which describes success as adaptations that support reductions in risk and vulnerability without compromising sustainability. Specifically, drawing on data collected from 209 coral reef tourism operators across 28 locations and eight countries in the Asia-Pacific, we explored how the risk, vulnerability, and sustainability outcomes that operators experienced one year after experiencing a severe climate disturbance (either coral bleaching or a cyclone) related to the types of adaptation they adopted in response to the disturbance. We used chi-squared tests and multivariate regression to explore the relationships between adaptive responses, adaptation outcomes, and contextual conditions. Compared to a control group with non-affected operators, operators affected by a climate disturbance were significantly more likely to have experienced an increase in perceived climate risk and reduced economic and environmental sustainability. However, our findings indicate that at least some adaptation responses were effective in promoting desirable outcomes, such as reductions in risk and vulnerability. Spatial diversification of reef site use supported economic outcomes despite environmental impacts, while reef restoration measures reduced perceived climate risks for some operators. Moreover, seeking support from others reduced vulnerability to coral bleaching, while also having positive economic outcomes. Our findings suggest scientific needs for further research on the causal relationships between adaptation measures and their outcomes, experimentation with different statistical methods, and empirical tests of the generalizability of our findings in different contexts over space and time.